A Scoping Review on On-Road Risks Associated with Driving with Dementia: Implications for Driving Technology Advancements - Carly May Walker; Makenzy Joy Herron; Alexander G. Mirnig; Andrew Kun; Sajay Arthanat (Applied Sciences)
Prolonging one’s ability to drive is a significant component of aging in place and personal autonomy. However, highly prevalent neurodegenerative conditions such as Alzheimer’s disease and related dementia among older people undermine the safety associated with driving and inevitably lead to their premature cessation of driving. This scoping review, based on PRISMA guidelines, extracted data from 40 research studies to highlight the on-road risks associated with driving with dementia or cognitive impairment. We identified 22 distinct risks, with speed compliance, navigation, lane adherence, turning, and stopping as the most reported risks in the identified studies. The study linked these risks to key cognitive domains and mapped out the scope of emerging driving technologies (semi-autonomous, autonomous, and aftermarket products) to address or mitigate the risks. The findings underscore the need to apply or create a framework for the design and development of inclusive driving interfaces to accommodate aging-related cognitive deficits.